Deconvoluting the Resident Mesenchymal Stromal Cell Niche for AT2 Stem Cells in Homeostasis and Disease in Adult Murine Lung - Taghizadeh, Sara; Justus Liebig University Giessen (My University, 2022)
Resident mesenchymal cells (rMCs defined as Cd31NegCd45NegEpcamNeg) control the proliferation and differentiation of alveolar epithelial type 2 (AT2) stem cells in vitro. The identity of this rMCs is still elusive. Among them, Axin2Pos mesenchymal alveolar niche cells (MANCs), which are expressing Fgf7, have been previously described. We propose that an additional population of rMCs, expressing Fgf10 (called rMC-Sca1PosFgf10Pos), are equally important to maintain AT2 stem cell proliferation. The alveolosphere model, based on the AT2-rMC co-culture in growth factor-reduced Matrigel, was used to test the efficiency of different rMC subpopulations isolated by FACS from adult murine lung to sustain the proliferation and differentiation of AT2 stem cells. We demonstrate that rMC- Sca1PosFgf10Pos cells efficiently promote the proliferation and differentiation of AT2 stem cells. Co-staining of the adult lungs for Fgf10 mRNA and Sftpc protein, respectively, indicate that 28% of Fgf10Pos cells are located close to AT2 cells. Co- ISH for Fgf7 and Fgf10 indicate that these two populations do not significantly overlap. Gene arrays comparing rMC-Sca1PosAxin2Pos and rMC-Sca1PosFgf10Pos support that these two cell subsets express differential markers. In addition, rMC function is decreased in obese ob/ob mutants compared to WT mice, with a much stronger loss of function in males compared to females. In conclusion, rMC- Sca1PosFgf10Pos cells are important in supporting AT2 stem cell proliferation and differentiation. This result sheds new light on the subpopulations of rMCs contributing to the AT2 stem cell niche in homeostasis and in the context of pre-existing metabolic diseases.
Keywords: Molecular Biology Medicine; ddc:610